Некоторые аспекты психологии манипуляции в сети интернет - Кривенко, М. А. (ХНУРЭ, 2012)
The given work is devoted to the manipulation in the internet, one of the main problems in the information society. Manipulators use psychological specifics of character of each person and use it for their own purposes. Internet also create new possibilities for spreading manipulators’ activities.